Indices of local community participation in forest management in South western Nigeria (2013)
Community Forestry (CF), a forest management initiative could help solve conflicting barriers to sustainable forest management. This paper reports the factors that will likely promote CF in southwestern Nigeria. Study sites were selected using purposive and random sampling techniques. Lagos State was purposively selected for the study based on its megalopolitan nature in addition to Osun, Ondo and Ogun states, which were randomly selected. Twenty percent (20%) of the Local Government Areas (LGAs) in the selected states were randomly sampled. Information was collected on demographic bio-data, socio-economic variables and participatory forest management indices from the local inhabitants in the sampled LGAs using structured questionnaire. Data obtained were analysed using descriptive and inferential statistics of the ratio scale model. Results revealed that respondents’ distribution was skewed towards the Yoruba ethnic group (92.9%); male gender (80.5%), one to five person household size (56.1%), married (87.5%) and illiterate (26.7%) population. Respondents were also mostly farmers (47.9%) associating more with cooperatives (45.0%) and with modal monthly income of between N10,000:00 and N15,000:00. Awareness about CF among the respondents was very low (23.8%) despite majority’s (70.8%) dependent on forest resources. Out of the fifteen indices of participation in community forest management (ranging from awareness of forestry project to contribution of human resource to maintenance of project) tested using the ratio scale model, awareness about forest project was the most important index of participation with mean People Participating Index (PPI) of 85. However, based on all indices of participation, Ondo state ranked highest with a PPI of 57.1% and Lagos ranked lowest (43.6%) in community participation in forest management. The study recommends more efforts at encouraging improvement in the indices of participation in forest management projects in the study area.